Major issues in the development of a Hacker's Code of Ethics / Ahmad Hafidz Baharom Alam Shah - Baharom Alam Shah, Ahmad Hafidz (2005)
The first day, the computer was invented. The next day it was hacked. This shows that hacking and computers are linked in a symbiosis relationship. The main problems facing hackers is the issues of professionalism and credibility. As early as the 1960s, hackers have started to develop guidelines and boundaries of their actions to prevent the use of hacking techniques for malicious purposes as well as to justify their actions towards corporate and government organizations. This code was later known as the hacker's code of ethics. Throughout the years, this code has evolved in line with the evolution of technology. However, the increases in malicious hackings of late have caused the public to view hacking as a threat to national security. Others have given the opinion that hacking is a necessary process to ensure the evolution of online security technology. This research also mentions the challenges in implementing a professional code of ethics for hackers.